Einige Fragen der Geometrie der Räume mit dem verallgemeinerten euklidischen Zusammenhänge - Bliznikas, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: B. Близникас. Некоторые вопросы геометрии пространств обобщенной евклидовой связности V. Bliznikas. Kai kurie apibendrinto euklidinio sąryšio erdvių geometrijos klausimai